2013
DOI: 10.1590/s1677-32252013000300001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of orofacial alterations in sickle cell disease: a review of literature

Abstract: Aim: To evaluate the manifestations of sickle cell disease on the orofacial complex through a review of current literature concerning prevalence of dental caries, periodontal disease, temporomandibular joint disorders and radiographic alterations of maxillofacial bones. Methods: Full-text papers retrieved from MEDLINE and LILACS electronic databases were critically reviewed. Results: Alterations of maxillofacial bones are well documented in the literature, but studies reporting caries, periodontal condition an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The link between these effects and PH has been confirmed by clinical and epidemiological studies (Caffey, ; Eng, ; Moseley, ; Ortner, ; Schultz, ; Stuart‐Macadam, ). In terms of skeletal samples, the state of cranial diploic bone in previously studied individuals with PH is described as either hypertrophic (Angel, ; Domínguez‐Rodrigo et al, ; Gowland and Western, ; Sullivan, ; Tayles, ; Walker et al, ; Wapler et al, ) or hyperplastic (Ascenzi, ; El‐Najjar et al, 1975; Filon, Faerman, Smith, & Oppenheim, ; Jatautis et al, ; Lagia, Eliopoulos, & Manolis, ; Lanzkowsky, ; Martin and Goodman, ; Moseley, ; Santos et al, ; Schultz, ; Stuart‐Macadam, ; Von Endt and Ortner, ; Walker, ; Walker et al, ; Williams, Lagundoye, & Johnson, 1975; Yildirim et al, ) due to an expanded diploë.…”
Section: Discussionmentioning
confidence: 99%
“…The link between these effects and PH has been confirmed by clinical and epidemiological studies (Caffey, ; Eng, ; Moseley, ; Ortner, ; Schultz, ; Stuart‐Macadam, ). In terms of skeletal samples, the state of cranial diploic bone in previously studied individuals with PH is described as either hypertrophic (Angel, ; Domínguez‐Rodrigo et al, ; Gowland and Western, ; Sullivan, ; Tayles, ; Walker et al, ; Wapler et al, ) or hyperplastic (Ascenzi, ; El‐Najjar et al, 1975; Filon, Faerman, Smith, & Oppenheim, ; Jatautis et al, ; Lagia, Eliopoulos, & Manolis, ; Lanzkowsky, ; Martin and Goodman, ; Moseley, ; Santos et al, ; Schultz, ; Stuart‐Macadam, ; Von Endt and Ortner, ; Walker, ; Walker et al, ; Williams, Lagundoye, & Johnson, 1975; Yildirim et al, ) due to an expanded diploë.…”
Section: Discussionmentioning
confidence: 99%
“…Caracas, et al reported a rare case of aseptic arthritis in the TMJ of a 22-year-old woman with SCD. The patient in this situation developed pain in the left preauricular region, hyperalgesia of the left masseter muscle, mouth opening limitation, and mild edema [31].…”
Section: Oral Mucosamentioning
confidence: 95%
“…In the calvarium the expanding bone marrow results in widening of the diploic space with thinning of the outer table. Perpendicular orientation of trabeculae to inner table gives a "hair-on-end" or "bristlelike" appearance [35], [71]. In a case-report by Acharya, the lateral skull radiograph of a 16-year old girl with SCD revealed thickened diploe and a ''hair-on-end pattern'' [39].…”
Section: F Malocclusion-facial Overgrowthmentioning
confidence: 99%